Discovery of ZrCoBi based half Heuslers with high thermoelectric conversion efficiency - Zhu, Hangtian; He, Ran; Mao, Jun; Zhu, Qing; Li, Chunhua; Sun, Jifeng; Ren, Wuyang; Wang, Yumei; Liu, Zihang; Tang, Zhongjia; Sotnikov, Andrei; Wang, Zhiming; et al. (Nature Communications, 2018)
Thermoelectric materials are capable of converting waste heat into electricity. The dimensionless figure-of-merit (ZT), as the critical measure for the material's thermoelectric performance, plays a decisive role in the energy conversion efficiency. Half-Heusler materials, as one of the most promising candidates for thermoelectric power generation, have relatively low ZTs compared to other material systems. Here we report the discovery of p-type ZrCoBi-based half-Heuslers with a record-high ZT of ∼1.42 at 973 K and a high thermoelectric conversion efficiency of ∼9% at the temperature difference of ∼500 K. Such an outstanding thermoelectric performance originates from its unique band structure offering a high band degeneracy (N v) of 10 in conjunction with a low thermal conductivity benefiting from the low mean sound velocity (v m ∼2800 m s-1). Our work demonstrates that ZrCoBi-based half-Heuslers are promising candidates for high-temperature thermoelectric power generation.
CRIS-Team Scopus Importer:2022-04-14